Hereditary Spherocytosis With Liver Transplantation After Cirrhosis: A Case Report - Yang, Xueliang; Wang, Wen; Fan, Wanhu; Cai, Lin; Ye, Feng; Lin, Shumei; Liu, Xiaojing (Frontiers in Medicine, 2022)
The clinical manifestations of hereditary spherocytosis are similar to those of various hemolytic anemias, which causes hereditary spherocytosis to be difficult to diagnose clinically. In this case, we obtained the peripheral blood of a patient and family members, and through a whole exome test of the 6297 genetic phenotypes confirmed by OMIM, we found a heterozygous nonsense mutation (c.4117C>T, P.Q1373X) in the SPTB gene. Combined with the patient's clinical data, the diagnosis was hereditary spherocytosis. Compared with the public population sequence database, the mutation was found to be unique. Through protein structure prediction analysis and literature studies, we found that the mutation may cause SPTB mRNA instability, resulting in insufficient spectrin protein synthesis and affecting the integrity and flexibility of the red blood cell membrane skeleton. This case report found that SPTB gene mutations may cause liver dysfunction and cirrhosis in addition to hereditary spherocytosis, and this finding expands the phenotypic spectrum of SPTB. This study confirmed that NGS can be used to diagnose hereditary spherocytosis. Identifying mutated genes can not only accurately treat diseases, but also avoid potential genetic risks and improve prenatal and postnatal care.